Pharmacological Activity of Betulinic Acid: A Systematic Literature Review - Himyatul Hidayah; Adawiyah, Nayla Robiatul; Surya Amal (HM Publisher, 2023)
Betulinic acid comes from betulin, a triterpenoid compound that naturally occurs in the bark of the Betula tree. Betulin has a pentacyclic chemical structure, which contains five distinct rings. Betulinic acid is the carboxylic acid form of betulin, meaning it has a carboxyl group (-COOH), which gives this compound its acidic nature. This study is a literature review. Data obtained from journal analysis in the form of qualitative and quantitative data. In this review article, the authors have explored in depth the promising pharmacological activities of betulinic acid. The studies that have been carried out consistently prove the potency of this compound in various therapeutic and pharmacological aspects. Research has also identified the ability of this compound to modulate biochemical pathways relevant to the nervous system, providing new hope in the treatment of complex neurological disorders.